2014
DOI: 10.1159/000356261
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Percutaneous Nephrolithotomy on an Ambulatory Basis

Abstract: Objective: Preliminary study to assess the feasibility and safety of percutaneous nephrolithotomy (PCNL) as an ambulatory procedure. Patients and Methods: Between February 2011 and September 2012, 84 patients with renal calculi fulfilling the inclusion criteria were admitted to the Urology Department of Benha University Hospitals for PCNL. All patients were subjected to a full medical history, clinical, laboratory and radiological examinations. Tubeless PCNLs were done in the supine position, and an antegrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
4
8
1
Order By: Relevance
“…The average operative time in our study was 80 ± 19.7 min (range of 50-120 min). The mean operative time was similar to the studies conducted by [19,24]. This higher mean operative time could be secondary to lengthier operative time taken for 4 cases of bilateral PCNL and 6 units of multipuncture PCNL.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The average operative time in our study was 80 ± 19.7 min (range of 50-120 min). The mean operative time was similar to the studies conducted by [19,24]. This higher mean operative time could be secondary to lengthier operative time taken for 4 cases of bilateral PCNL and 6 units of multipuncture PCNL.…”
Section: Discussionsupporting
confidence: 78%
“…In two patients, stone was there in upper and lower calyx and in two others, stone was in middle and inferior calyx. In the study done by El-Tabey et al, most of the stones were located in the renal pelvis -50% (42), followed by inferior calyx-28.6% (24) and then partial staghorn-21.4% [19].…”
Section: Discussionmentioning
confidence: 96%
“…7%, p = 0.36). Sufficient evidence exists to suggest tubeless PNL to be equivalent or even superior to standard PNL for a select group of patients [ 7 ]. Various adjuncts have been tried to enhance hemostasis of the percutaneous tract, one of which is insertion/ instillation of hemostatic agents into the tract including oxidized cellulose, gelatin sponge, gelatin granules plus thrombin and fibrin glue [ 8 – 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alyami et al reported that 66% of their cases could be safely discharged after an overnight stay [ 20 ]. In the study by Tabey and colleagues, 71.4% of the cases could be safely discharged from the hospital within 24-hours postoperatively [ 7 ]. Relatively higher proportion of cases could be discharged within 24 hours of surgery in our series.…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 97 articles, nine (n = 502) were selected, which satisfied our predefined search criteria (Tables 1 and 2) [8][9][10][11][12][13][14][15][16]. Four studies (n = 209) discharged patients on the same day as surgery (group 1) [8][9][10][11], and five studies (n = 293) discharged patients after an overnight stay (group 2) [12][13][14][15][16]. These included three case series, five cohort studies, and one randomised trial.…”
Section: Evidence Synthesismentioning
confidence: 99%